Vannamei shrimp Litopenaeus vannamei mortality correlation with water quality dynamics and blue-green algae in earthen pond - Rahmatulloh Arifin; Kukuh Nirmala; Yuni Puji Hastuti; Eddy supriyono (Indonesian Society of Scientific Aquaculture (ISSA), 2026)
Mortality represents a significant challenge in enhancing productivity in intensive vannamei shrimp (Litopenaeus vannamei) farming systems. In ponds with soil bottoms, shrimp mortality is often caused by poor water quality, influenced by fluctuations in physicochemical parameters and changes in phytoplankton communities. This study aims to analyze the correlation between water quality, phytoplankton succession, and shrimp mortality. Pond water samples (E9, E10, F9, F10, and F11) were collected periodically to measure key physicochemical parameters, such as temperature, pH, dissolved oxygen (DO), ammonia (NH3), total ammonia nitrogen (TAN), and nitrite (NO2), as well as the abundance and dominance of phytoplankton. The results showed that shrimp mortality positively correlated with plankton abundance (0.57) and the presence of Blue-green Algae (0.43) in the water. Further, descriptively, shrimp mortality followed a similar pattern across several observation ponds, with deaths occurring after the decline or disappearance of Blue-green algae from previous observations. The water quality parameters that correlated with plankton abundance and blue-green algae dominance included TAN, BOD, and turbidity. The transformation in phytoplankton dominance to Blue-green algae can increase BOD levels and produce toxic compounds upon lysis, which may disrupt physiology and lead to shrimp mortality. These results underscore the importance of water quality management and phytoplankton monitoring to reduce vannamei shrimp mortality. Keywords: Blue-green algae, correlation, earthen pond, Vaname shrimp, water quality Abstrak Kematian merupakan tantangan dalam meningkatkan produktivitas pada kegiatan budidaya udang vaname (Litopenaeus vannamei) dengan sistem intensif. Pada kolam budidaya dengan dasar kolam tanah sering kali kematian udang disebabkan oleh kualitas air yang buruk, yang dipengaruhi oleh fluktuasi parameter fisikokimia dan perubahan komunitas fitoplankton. Penelitian ini bertujuan untuk menganalisis korelasi antara kualitas air, suksesi fitoplankton, dan mortalitas Litopenaeus vannamei. Sampel air kolam budidaya (E9, E10, F9, F10 dan F11) diambil secara berkala untuk mengukur parameter fisikokimia utama, seperti suhu, pH, DO, amonia (NH3), TAN dan nitrit (NO2), serta kelimpahan dan dominansi fitoplankton. Hasil penelitian menunjukkan mortalitas udang memiliki nilai korelasi positif dengan kelimpahan pankton (0,57) dan Blue-green Algae (0,43) yang ada pada perairan. Selain itu secara deskriptif kematian udang memiliki pola yang sama pada beberapa kolam pengamatan dimana kematian terjadi setelah terjadinya kematian atau berkurangnya kelimpahan Blue-green Algae dari pengamatan sebelumnya. parameter kualitas air yang memiliki nilai korelasi terhadap kelimpahan plankton dan dominasi Blue-green Algae yaitu TAN, BOD dan Kecerahan. Pergeseran dominansi fitoplankton ke Blue-green algae dapat meningkatkan BOD dan menghasilkan senyawa toksik ketika lisis yang dapat mengganggu fisiologi hingga menyebabkan kematian udang. Temuan ini menekankan pentingnya pengelolaan kualitas air dan pemantauan fitoplankton untuk mengurangi mortalitas udang vaname. Kata kunci: blue-green algae, korelasi, kolam tanah, kualitas air, udang vaname